Self‐esteem and other‐esteem in college students with borderline and avoidant personality disorder features: An experimental vignette study. (24th April 2013) - Bowles, David P.; Armitage, Chris J.; Drabble, Jennifer; Meyer, Björn
ABSTRACT An experimental study investigated self‐esteem and other‐esteem responses to either fully supportive or less supportive interpersonal feedback in college students with avoidant and borderline personality disorder features (APD and BPD respectively). Disturbances in self‐esteem and in evaluations of others are central to definitions of both APD and BPD, but the extent to which such interpersonal appraisals are responsive to contextual features, such as evaluative feedback from others, is not yet clear. In theory, we would expect that individuals with pronounced PD features would show more inflexible and more negative self‐evaluations and others‐ evaluations than those without PD features. In this study with 169 undergraduates, APD but not BPD features were associated with other‐contingent state self‐esteem and other‐esteem. A significant interaction indicated that highly avoidant respondents felt particularly negatively about themselves and their close others in situations that conveyed subtle criticism but not in situations signalling unequivocal support. This suggests that their self‐esteem and other‐esteem, rather than being rigidly negative, are instead highly contingent upon interpersonal feedback. Such context contingency has implications for the trait‐like description of diagnostic characteristics within current taxonomies and is in line with contemporary dynamic models of personality structure and process. Copyright © 2013 John Wiley & Sons, Ltd.